Disruption of CLPB is associated with congenital microcephaly, severe encephalopathy and 3-methylglutaconic aciduria. Issue 5 (3rd February 2015) - Capo-Chichi, José-Mario; Boissel, Sarah; Brustein, Edna; Pickles, Sarah; Fallet-Bianco, Catherine; Nassif, Christina; Patry, Lysanne; Dobrzeniecka, Sylvia; Liao, Meijiang; Labuda, Damian; Samuels, Mark E; Hamdan, Fadi F; et al.
Abstract : Background: The heterogeneous group of 3-methylglutaconic aciduria disorders includes several inborn errors of metabolism that affect mitochondrial function through poorly understood mechanisms. We describe four newborn siblings, from a consanguineous family, who showed microcephaly, small birth weight, severe encephalopathy and 3-methylglutaconic aciduria. Their neurological examination was characterised by severe hypertonia and the induction of prolonged clonic movements of the four limbs upon minimal tactile stimulation. Methods and results: Using homozygosity mapping and exome sequencing, we identified a homozygous truncating mutation (p.I562Tfs*23) in CLPB segregating with the disease in this family. CLPB codes for a member of the family of ATPases associated with various cellular activities (AAA + proteins) whose function remains unknown. We found that CLPB expression is abolished in fibroblasts from the patients. To investigate the function of this gene, we interfered with the translation of the zebrafish clpb orthologue using an antisense morpholino. The clpb morphants showed an abnormal touch-evoked response with increased swim velocity and tail beat frequency. This motor phenotype is reminiscent of that observed in the patients and is suggestive of increased excitability in neuronal circuits. Interestingly, knocking down clpb reduced the number of inhibitory glycinergic interneurons and increased a population of excitatory glutamatergic neurons in the spinal cord. Conclusions: Altogether, our study suggests that disruption of CLPB causes a novel form of neonatal encephalopathy associated with 3-methylglutaconic aciduria.